The new chronic pain MG30 category and diagnostic specificity in quality registries—problems and suggested solutions with special reference to Swedish Quality Registry for Pain rehabilitation (SQRP) - Bäckryd, Emmanuel; Novo, Mehmed; Hallsén, Johanna; Schultze, Stefan; Rivano Fischer, Marcelo; Gerdle, Björn (Frontiers in Pain Research, 2024)
The Swedish Quality Registry for Pain rehabilitation (SQRP) is a well-established clinical registry for adult patients with complex chronic pain conditions. SQRP registers patient-reported outcome measures from a majority of specialist chronic pain units/departments in Sweden. Up to four International Classification of Diseases version 10 (ICD-10) diagnoses can be registered in SQRP. The aim of the paper is to describe how we envision the new chronic pain category MG30 in ICD-11 can be used in SQRP. We envision that the first diagnosis in SQRP shall always be a MG30 diagnosis, which will ensure broad implementation of ICD-11 in Swedish pain care. However, at first glance, there seems to be specificity problems with ICD-11 codes that might impair their useability in SQRP or other registries. But ICD-11 offers more than meets the eye. First, the entries at the level of the so-called foundational layer have unique resource identifiers (URI) that can be used to enhance specificity. Second, ICD-11 contains numerous extension codes that can be combined with the MG30 codes – for instance, concerning the anatomical location of pain. Third, to enrich the description of the clinical concept at hand, it is possible to create clusters of stem codes. These three options are briefly discussed. We conclude that the full potential of the MG30 category can be better exploited in registries such as SQRP if foundational codes, extension codes, and/or clustering of stem codes are used to enhance diagnostic specificity.